Full marathon after bilateral total hip arthroplasty: case report with magnetic resonance imaging findings - Ran Zhao; Zhu, Weiguo; Cai, Hong; Yanqing Liu (Journal of the Pakistan Medical Association, 2025)
Long-distance running is not a recommended form of exercise after total hip arthroplasty (THA). However, younger and more active patients often wish to return to sport after THA. We present the case of a 38-year-old man who underwent bilateral THA for osteonecrosis. Three months after surgery and rehabilitation, the patient returned to his normal life. He returned to sport one year after surgery when he engaged in long-distance running and documented his daily exercise status. In the fourth year after surgery, he completed a full marathon race with a total length of 42.2km. Magnetic resonance imaging of the bilateral hip joints performed within 48 hours after the marathon revealed no oedema in the greater trochanteric region and a small amount of fluid accumulation in the hip joints. Bilateral THA achieved excellent clinical and radiographic results based on clinical manifestations and magnetic resonance imaging. Keywords: Total hip arthroplasty; Magnetic resonance imaging; Long-distance running; Return to sport.